Un mundo huérfano by Giuseppe Caputo: the Reconfiguration of the Fragmented Body Through Representation - Díaz Ibáñez, Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article aims —from a critical reading of the novel by the writer Giuseppe Caputo (Barranquilla, 1982) entitled Un mundo huérfano (2016)— to trace the presence and dialogue that is established in it with the category of a defined body, according to the scope of queer theory, such as performance and theatricality, in which neither gender nor sex are determining factors, and in which two interests of the author play an important role: the oxymoron and fragmentation to operate the reconstruction of said body that also reads as text.